”Akan Setia Pada Bumi” Sebagai Etika Ekologi (Keseimbangan Antara Manusia dan Alam dalam Pemikiran Nietzsche): "Will Be Loyal to the Earth" as Ecological Ethics (Balance Between Humans and Nature in Nietzsche's Thought) - Riko, Albertus (Jurnal Filsafat Indonesia, 2024)
The critical thinking disposition is one of the key abilities for success in the global competition of the 21st century. This concept refers to the extent to which a person has a tendency to be skeptical, gather more evidence, and analyze the information encountered. This disposition is generally shared by the students and the scholars in philosophy or a society with a high appreciation of philosophy, science and secularism. Recently there has been an interest in looking more deeply and empirically at the influence of social aspects such as religion and culture on critical thinking disposition. Conflicting research results were found showing the positive and negative influence of religion on critical thinking dispositions. These mixed results indicate the possibility of the presence of a mediator variable that can change the direction of the relationship or influence between the two variables. This research is interested in examining the influence of religiosity on critical dispositions through two pathways. The first path is the direct path of the two variables. Meanwhile, the second path is the path mediated by epistemic beliefs and epistemic emotions. It is hoped that this research can develop an explanation of the various and contradictory findings regarding the relationship or influence between the variables of religiosity and critical disposition. The research results show that epistemic beliefs can be a partial mediator for the causal relationship between religiosity and critical thinking disposition. However, epistemic emotions cannot be a mediator for both variables. These results show that religion, especially in Indonesian Muslim, has a significant influence on a person's critical attitude and that influence can become stronger if accompanied by contextualist epistemic.